К вопросу о создании физической модели процесса трения при глубоком сверлении материалов - Маршуба, Вячеслав Павлович; Маршуба, О. В. (НТУ "ХПИ", 2006)
The physical model of process of friction is offered at treatment of different materials depending on influencing of the physical phenomena in the zone of cutting and zone of treatment. The offered physical model is intended for making of general mathematical model, which describes the process of the deep boring in different materials. The utilizing of this physical model will allow determining the necessary terms of treatment of the deep openings with the burst performance at treatment of details from different materials.
Keywords: инструмент режущий; стружка; резание; адгезия